The Polyvalent Heat Supply System for Passive-Type Experimental Building (area of 300 m2) Based on Renewable and Alternative Energy Sources - Basok, B.I.; Bozhko, I.K.; Belyaeva, T.G.; Goncharuk, S.M.; Nedbailo, O.M.; Novitska, M.P.; Tkachenko, M.V.; Khybyna, M.A. (Science and Innovation, 2024)
The results of development and implementation of heat supply system for experimental building of passive type have been presented; the optimal operating conditions have been studied; and guidelines for the creation of heat supply systems for passive type buildings have been elaborated.